2022
DOI: 10.1038/s41598-022-09146-4
|View full text |Cite
|
Sign up to set email alerts
|

Ornithophily in the subtribe Maxillariinae (Orchidaceae) proven with a case study of Ornithidium fulgens in Guatemala

Abstract: Ornithophily has been long speculated to occur in the subtribe Maxillariinae (Orchidaceae), relying either solely on micromorphological analyses or scarce field observations of undefined species. In Guatemala we were able to observe regular visits of the azure-crowned hummingbirds feeding on flowers of Ornithidium fulgens. These observations have led us to investigation of floral attractants by means of scanning and transmission microscopy, histochemical and chemical analyses (GC–MS). Conducted investigation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Crucial observations have been made during the field research in Guatemala, where azure-crowned hummingbirds ( Amazilia cyanocephala ) have been spotted while pollinating flowers of Ornithidium fulgens Rchb. f. This finding was later supported by the results of micromorphological, histochemical, and chemical studies [ 9 ].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Crucial observations have been made during the field research in Guatemala, where azure-crowned hummingbirds ( Amazilia cyanocephala ) have been spotted while pollinating flowers of Ornithidium fulgens Rchb. f. This finding was later supported by the results of micromorphological, histochemical, and chemical studies [ 9 ].…”
Section: Introductionmentioning
confidence: 61%
“…ex R.Br. [ 8 ], O. fulgens [ 9 ], and Maxillaria anceps Ames & C. Schweinf [ 6 ]. Davies et al [ 6 ] estimate that within the core of the subtribe only 8% of species produce nectar.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, G. valida does not present floral traits suggestive of hummingbird pollination. Typical hummingbird-pollinated flowers are tubular, red-or orange-colored, and scentless and present high volumes of diluted nectar (Abrol, 2012;Dudash et al, 2011;Faegri & van der Pijl, 1979;Lipi nska et al, 2022), as reported in S. lanceolata, an orchid pollinated by three hummingbird species (Singer & Sazima, 2000). Nevertheless, recent evidence shows hummingbirds pollinating and feeding on "atypical" flowers that provide significant support for their residency and long-distant migration (Maruyama et al, 2013;Waser et al, 2018).…”
Section: Pollinators and Pollination Behaviormentioning
confidence: 95%
“…Orchids are one of the most amazing and intriguing examples of pollinator interactions (Tremblay, 1992) and are among the most specialized plants with respect to their pollination (Schiestl and Schlüter, 2009;Phillips et al, 2009Phillips et al, , 2011Castro and Singer, 2019;Lipińska et al, 2022). It is estimated that about 60% of orchids interact with a single species of pollinator (Tremblay, 1992).…”
Section: Importance Of Interaction With Pollinatorsmentioning
confidence: 99%
“…Ornithophilous orchids usually have a callus that partially closes the floral tube at the level of the anther and the stigma (van Der Pijl and Dodson, 1966). The pollen sacs of most orchids are yellow, but this yellow would produce a high visual contrast with the color of the bill and hummingbirds would be stimulated to clean their bills, implying crossbreeding failure in orchids (Lipińska et al, 2022). That is why, to avoid detection, a large part of the orchids pollinated by hummingbirds evolved to have a dark pollinarium (Dressler, 1971).…”
Section: Birdsmentioning
confidence: 99%